Board of Editor - Journal of Infrastructure & Facility Asset Management (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
Board of Editor PATRON : Dean - Faculty of Civil, Environmental, Earth Sciences - ITS.Head Training Center Management & Functional Position - Ministry of PWPH. RESPONSIBLE : Head of Department – Civil Engineering Department - ITSBOARD OF EDITOR Chief Editor : Ria Asih Aryani Soemitro ITS, Indonesia h-index (GS = 10)Founding Editor : Hitapriya Suprayitno ITS, Indonesia h-index (GS = 8) Managing Editor : Trihanyndio Rendy Satrya ITS, Indonesia h-index (GS = 2) Mahendra Andiek Maulana ITS, Indonesia h-index (GS = 2)Editor : Data Iranata ITS, Indonesia h-index (GS = 3) Alex Abdi Chalik PUPR, Indonesia h-index (GS = -) Danang Parikesit UGM, Indonesia h-index (GS = 7) Maimunah Sapri UTM, Malaysia h-index (GS = 15) Wahyu Caesarendra UBS, Brunei Dar es Salam h-index (GS = 17) Address : Editor JIFAM – Room J - 201 Departement of Civil Engineering Institut Teknologi Sepuluh Nopember ITS Campus, Sukolilo, Surabaya 60111 Email: jurnal.jifam@gmail.com Website: https://iptek.its.ac.id/index.php/jifam